2019
DOI: 10.1007/978-3-030-24766-9_28
|View full text |Cite|
|
Sign up to set email alerts
|

Guess Free Maximization of Submodular and Linear Sums

Abstract: We consider the problem of maximizing the sum of a monotone submodular function and a linear function subject to a general solvable polytope constraint. Recently, Sviridenko et al. [16] described an algorithm for this problem whose approximation guarantee is optimal in some intuitive and formal senses. Unfortunately, this algorithm involves a guessing step which makes it less clean and significantly affects its time complexity. In this work we describe a clean alternative algorithm that uses a novel weighting … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 19 publications
0
6
0
Order By: Relevance
“…Existing hardness results imply that no multiplicative approximation guarantees are possible in polynomial time for maximizing a potentially negative submodular function with or without constraints [13,31]. 1 Nevertheless, the objective function we consider has some structure that has been exploited in previous works [14,17,34]. These works have shown that in this case we should aim for a weaker notion of approximation and find a solution Q satisfying…”
Section: Related Workmentioning
confidence: 99%
See 4 more Smart Citations
“…Existing hardness results imply that no multiplicative approximation guarantees are possible in polynomial time for maximizing a potentially negative submodular function with or without constraints [13,31]. 1 Nevertheless, the objective function we consider has some structure that has been exploited in previous works [14,17,34]. These works have shown that in this case we should aim for a weaker notion of approximation and find a solution Q satisfying…”
Section: Related Workmentioning
confidence: 99%
“…One of the main downsides of these algorithms is that the running time can be prohibitive. The works [14,34] propose algorithms based on the continuous greedy algorithm that maximizes the multilinear extension, a continuous function extending the submodular function to the domain [0, 1] n . The multilinear extension is expensive to evaluate and the continuous greedy algorithm requires many iterations to converge.…”
Section: Related Workmentioning
confidence: 99%
See 3 more Smart Citations